Study on Understanding the Role of Non-state Education Providers in Somalia - World Bank (World Bank, Washington, DC, 2019)
This document presents the findings of a Study on Understanding the Role of Non-State Education Providers in Somalia commissioned by the World Bank. The goal of the study was to develop an evidence base for understanding non-state education providers in the broader Somali education ecosystem, and to identify opportunities for cooperation between state and non-state actors. The study focuses on formal primary and secondary schools in urban and peri-urban areas across four locations in Somalia: Mogadishu (Benadir Regional Administration), Kismayo (Jubbaland), and Garowe and Bosasso (Puntland). The overall objective of this study is to help relevant Somali government institutions and the international community in developing an evidence base for understanding non-state education providers in the broader Somali education ecosystem, and in identifying opportunities for streamlining private initiatives into federal and state-level education sector development policy. The report is divided into three main chapters: an overview of Somalia’s education sector and its implications on study methodology, presentation of the study’s findings, and key research implications.